Impact of Tregs on tumor regression in locally advanced G/GEJ cancer patients undergoing neoadjuvant chemoimmunotherapy - Yong Zhang; Chaoji Zhang; Peng Qin; Baozhen Ma; Anqi Lyu; Fang Zhang; Tiepeng Li; Lu Han; Yiman Shang; Zibing Wang; Quanli Gao; Lingdi Zhao (Scientific Reports)
Abstract Neoadjuvant chemoimmunotherapy has transformed the treatment of locally advanced gastric or gastroesophageal junction (G/GEJ) cancer. However, identifying reliable predictive markers for treatment efficacy remains challenging. We conducted a retrospective analysis to evaluate the prognostic value of peripheral blood regulatory T (Treg) cells in patients with G/GEJ cancer undergoing neoadjuvant chemoimmunotherapy followed by curative resection. From July 2020 to May 2023, 79 patients met the inclusion criteria. All patients achieved R0 resection following D2 radical surgery, with 26.6% exhibiting a pathological complete response (pCR). Significant differences in Treg cells, T/Treg ratios, and CD4+/Treg ratios were observed between patients with pCR and those without after one treatment cycle (P = 0.0054, 0.0489, and 0.0434, respectively). Patients were categorized based on changes in Treg cell counts post-treatment, revealing a higher pCR rate in those with reduced Treg cells (P = 0.014). Changes in Treg cell counts after one cycle of neoadjuvant chemoimmunotherapy serve as a promising predictive marker for pCR in locally advanced G/GEJ cancer patients. This finding supports the development of personalized treatment strategies, enhancing outcomes in this challenging clinical landscape.